A Review Of Big Data Analytic In Healthcare - et. al., Nouf Ali AL Ajmi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Big data analytics (BDA) has been proven to be useful in various fields such as sports, and healthcare data. Healthcare data is increasingly being digitized today and the data collected today is coming in from modern devices. It has reached a significant volume all over the world. There is increased interest in the reuse of Big Data technology in the healthcare industry to manage massive collections of heterogeneous health datasets. BDA is of paramount importance in healthcare aspects such as patient diagnostics, fast epidemic recognition, and improvement of patient management.This paper aims to provide an overview of the BDA concept in the healthcare field and to show different aspects of BDA in healthcare like architectural framework, analysis models, tools, and applications.